Clinical outcomes of the reverse McLaughlin procedure for Hill–Sachs lesions in anterior shoulder instability. (8th December 2018) - Han, Fucai; Chin, Brendan Yi Yao; Tan, Bryan Hsi Ming; Lim, Chin Tat; Kumar, V Prem
Introduction: Engaging Hill–Sachs lesions in recurrent anterior shoulder dislocation have been managed with the remplissage procedure. Clinical and cadaveric studies have reported limitation of rotation after this procedure. We introduce the reverse McLaughlin procedure where the infraspinatus and the underlying capsule are detached and approximated into the Hill–Sachs defect with transosseous sutures. This is a preliminary report using this technique. Methods: Seventeen patients with recurrent anterior shoulder dislocations and an engaging Hill–Sachs lesion underwent a Bankart repair and remplissage procedure (n = 9) or the reverse McLaughlin procedure ( n = 8). Patients were evaluated using the SF-36, American Shoulder and Elbow Surgeons (ASES), and Constant scores. Clinical assessment of the shoulders was also performed. Results: At the final follow-up, all patients in both groups achieved comparable clinical outcome scores. No significant differences were reported in the range of motion of the shoulders between the two groups. There was one dislocation of the operated shoulder in each group after an injury. Conclusion: The reverse McLaughlin procedure for engaging Hill–Sachs lesions is simple, easy to perform, and associated with functional outcomes and range of motion at least equivalent to those obtained via the remplissage technique. It may be an alternative to the latter procedure. Level of Evidence: III, Retrospective Comparative Study